STUDY OF SPILWAY AS ALTERNATIF FLOOD CONTROLLER ZONES IN LOK BAHU SAMARINDA - BUDI SATRIYO, PANDU (KURVA S JURNAL MAHASISWA, 2014)
ABSTRACT                    Flooding is a natural phenomenon that is common in a region which many in aliri by the flow of the river . In simple terms the flood can be defined as the presence of water in a vast region that covers the area of the earth 's surface.                    Lok Bahu area is an area of industry , trade , construction , housing is a growing area , so that in the event of flooding , it can hamper economic growth Lok Bahu society . So we need a quick and appropriate action in dealing with the floods in the Lok Bahu.                    Methods for calculating the design rainfall is the method of Gumbel and Log method of Person type III . While the method is to determine the design flood discharge is Rational Method . Alternatives offered for flood control in the Lok shoulder is to build a spillway , which point to accommodate the existing flood discharge.                    From the results of calculations can be concluded that , the dimensions of the spillway plan is wet 2 meters high , bottom width of 7 meters and is 1.06 meters high surveillance . Dimensional channel this plan is estimated to be able to accommodate the flood discharge design of the next 25 years . But while waiting for the construction of the canal realized right steps are done Karang Asam river normalization in the region of the Lok Bahu.